Reliability-based evaluation for concrete-filled steel tubular (CFST) truss under flexural loading. (June 2020) - Chen, Silin; Hou, Chao; Zhang, Hao; Han, Lin-Hai; Mu, Ting-Min
Abstract: Concrete-filled steel tubular (CFST) truss is now widely used in many large-span constructions. In the past, relevant studies on the reliability of CFST structures mostly focused on structural components such as individual columns and beams. In current practices, a simplified method based on the ultimate axial strengths of the chords is commonly adopted to predict the flexural strength of a CFST truss, since there is no mature system-based design regulations nor reliability evaluations on this complex composite system. This paper aims to address this gap by advanced structural reliability analysis of CFST truss through numerical approach considering both the structural nonlinearities and random uncertainties. The finite element models are validated against experimental results. Afterwards, a mass finite element simulation, taking into account the material and geometric nonlinearities, random initial imperfections and potential finite element model errors, is conducted to generate the statistics of the flexural strengths of CFST trusses. Reliability analysis is then conducted to calculate reliability indexes in respect of different resistance factors under various load cases based on AASHTO. Finally, reliability-based evaluation on the safety level of CFST truss design according to mainstream design guidelines such as ANSI/AISC 360–16, Eurocode 4:2004 and JGJ/T D65–06–2015 are carried out. Results show that the current component-based strength prediction of CFST trusses meet the target reliability while the current regulations provide uniform reliability. Highlights: Numerical approach for CFST truss with random uncertainties is established. Reliability analysis and system resistance factors for CFST truss based on FORM are presented. A reliability-based evaluation for CFST truss design methods in three guidelines is conducted.